Ayurvedic Management of Uterine Fibroid - Behera Swetanjali; Meher Sudeshna; Samal Jitendra (International Journal of Ayurveda and Pharma Research, 2025)
Fibroid is the most common benign solid tumour of the uterus in female. Histologically, this tumour is composed of smooth muscle and fibrous connective tissue, so named as Uterine leiomyoma, myoma or fibromyoma. According to the U.S. National Institutes of Health (NIH) 20-25% of women of reproductive age have fibroids. The aetiology still remains unclear. The prevailing hypothesis is that, it arises from the neoplastic single smooth cells of the myometrium. It can be related to Garbhasaya Granthi or Arbuda. The presented case involves a 43 years old female patient who approached the outpatient department with complaints of menorrhagia with clots and pain in left iliac region. On the basis of sign and symptoms, USG had shown bulky uterus measuring 9.6×4.6×6.6cm and a mixed echoic mass measuring 3.3×2.4cm seen in middle part of uterus, which is a fibromyoma. After having a thorough examination, the patient underwent Ayurvedic treatment protocol, including Sodhana chikitsa, oral medication and dietary modifications. After three months, the patient reported symptomatic relief and an ultrasound report with size of uterus i.e. 8.2×5.5×4.4 cm and a small intramural fibroid of size 15mm.